Penguatan Ketahanan Ekonomi Masyarakat Penjaringansari Surabaya Melalui Pengembangan Usaha Produktif Wolkaponik - Setyaningrum, Idfi; Kartini, Kartini; Rahardjo, Seto Sugianto Prabowo (LPPM Universitas Narotama, 2024)
The community service program in RT 02 RW 04 Penjaringansari, Surabaya, aims to tackle the challenges of population growth and global climate change by promoting urban farming, fish cultivation, and the use of family medicinal plants (TOGA). This initiative helps strengthen family economic resilience by utilizing home gardens, while also contributing to sustainable development or the Green Economy. However, the program faces several issues, such as the lack of productive business development, uncertain quality of herbal products, and the absence of integrated management between plant and fish cultivation. The proposed solutions include business development through creating a proper business model, integrating urban farming with aquaponics using Wolkaponik technology, and improving the quality and certification of herbal products. The results show increased community knowledge of integrated farming technology, herbal product training, and the formation of an urban farming group with a vision of a nature-friendly lifestyle. The program also involves students in mentoring and training, yielding positive impacts on food security, environmental aesthetics, and local community welfare.